Effects of Climate Change on Environmental Security among Vulnerable Groups in Zango Kataf Local Government Area of Kaduna State - Ibrahim MUSA; Abiola Titus OLUSOLA; Sule MAGAJI (Loka: Journal Of Environmental Sciences, 2024)
Purpose:This study explores the impacts of climate change on environmental security among vulnerable populations in the Zangon Kataf Local Government Area of Kaduna State, Nigeria.Methodology:Using a cross-sectional survey design, data were collected through a combination of structured questionnaires, in-depth interviews, and the analysis of secondary data sources. The area under study lies within a tropical grassland zone, which has witnessed notable climatic changes in recent decades, particularly concerning temperature and rainfall patterns.Findings:Findings reveal a steady increase in annual surface temperature, showing a 12% average rise between 1989 and 2022. At the same time, the annual rainfall in the region has been on a downward trend, decreasing by approximately 4.88% over the same period. These climatic changes pose significant challenges to environmental security in the area, especially for groups that are economically and socially vulnerable.Implication:The study emphasizes the urgent need for climate adaptation and mitigation strategies focused on these populations. Policy recommendations include climate-smart agriculture, awareness programs, and the provision of support systems to build resilience and enhance long-term environmental security in the face of ongoing climate change.